Original and strengthened traditional timber connections - Branco, Jorge M. (2009)
A series of monotonic and cyclic tests on unstrengthened full-scale specimens were performed in order to characterize the original behavior of connections representative of traditional timber trusses. Subsequently, connections strengthened with metal devices were tested under monotonic and cyclic loading. Tests on assembled connections were preceded by accurate material characterization, in terms of the mechanical properties of the timber elements used for all full-scale models. The experimental study was complemented by a numerical analysis using FEM, through parametric studies that followed the models calibration process.